Multiple Giant Coronary Arterial Aneurysms Leading to Stable Angina - Bahadir Sarli; Eyup Ozkan; Melih Demirbas; Ahmet O Baktir (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2015)
Coronary artery aneurysm (CAA) is defined as abnormal dilatation of a coronary artery luminal diameter to 1.5 to 2 times wider than the adjacent normal segment. Giant coronary artery aneurysms are rare, with a reported prevalence of 0.02% to 0.2% [1]. Most of the giant coronary artery aneurysms are asymptomatic, but some patients present with angina pectoris, sudden death, fistula formation, pericardial tamponade, compression of surrounding structures, or congestive heart failure. A 61-year-old man referred to our outpatient clinic with stable angina pectoris lasting approximately 3 months, rising with exercise and relaxing with resting. He had no cardiovascular risk factor except smoking a pack/ day for 10 years. ECG revealed right bundle branch block and no signs of acute ischemia. Transthoracic echocardiography showed normal LV wall motion and a normal ascending aorta in diameter. Optimal medical treatment (OMT) for stable angina pectoris including acetyl salicylic acid, metoprolol and rosuvastatin was initiated immediately. However, angina continued despite a short course of OMT. Then coronary angiography was planned to identify options for revascularization. Coronary angiography revealed giant coronary aneurysms on the proximal left anterior descending artery (20 X 18 mm) and circumflex artery (16 X 20 mm) and accompanying atherosclerotic stenosis adjacent to the aneurysms (Figure 1). Hs- CRP was measured 4.5 mg/L. Antinuclear antibody, anti-ds-DNA level, and p-ANCA and c-ANCA levels were in normal range. Because our patient had multivessel CAD and SYNTAX score was 30, heart team considered CABG was more beneficial for this patient and accordingly he was transferred to cardiovascular surgery (CVS) department for CABG.